2009
DOI: 10.1590/s1519-69842009000500019
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the genotoxic potential of Austroplenckia populnea (Reiss) Lundell chloroform fraction from barkwood extract in rodent cells in vivo

Abstract: The genotoxic effect of the Austroplenckia populnea chloroform fraction from barkwood extract was tested in vivo on peripheral blood cells of Swiss mice with the comet assay (SCGE), and the clastogenic effect was investigated on peripheral blood cells of Swiss mice and bone marrow cells of Wistar rats, with the micronucleus and chromosome aberrations tests. The animals were treated by gavage with 3 concentrations of the extract: 300, 600 and 900 mg.kg -1. Peripheral blood cells of Swiss mice were collected 4 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…Recently, using the micronucleus test in mice bone marrow, our research team revealed that the three fractions of S. crassifolia studied in the present work (HE, EA and HA), did not cause significant increase in the frequency of micronucleated polychromatic erythrocytes compared to the solvent control group (Carneiro et al, 2013). Flammang et al (2006) and Ribeiro et al (2009) also did not found any statistically significant induction in micronucleated polychromatic erythrocytes of mice bone marrow treated with root extract of S. oblonga and bark extract of Austroplenckia populnea (Reiss) Lundell (Celastraceae), respectively. In culture of peripheral blood lymphocytes from rat, any induction of chromosomal aberrations was not found after 90 consecutive days of treatment with root extract of S. oblonga (Flammang et al, 2007).…”
Section: Resultsmentioning
confidence: 45%
“…Recently, using the micronucleus test in mice bone marrow, our research team revealed that the three fractions of S. crassifolia studied in the present work (HE, EA and HA), did not cause significant increase in the frequency of micronucleated polychromatic erythrocytes compared to the solvent control group (Carneiro et al, 2013). Flammang et al (2006) and Ribeiro et al (2009) also did not found any statistically significant induction in micronucleated polychromatic erythrocytes of mice bone marrow treated with root extract of S. oblonga and bark extract of Austroplenckia populnea (Reiss) Lundell (Celastraceae), respectively. In culture of peripheral blood lymphocytes from rat, any induction of chromosomal aberrations was not found after 90 consecutive days of treatment with root extract of S. oblonga (Flammang et al, 2007).…”
Section: Resultsmentioning
confidence: 45%
“…A. populnea hydroalcoholic leaf extract evaluated using the micronucleus test and chromosome aberration assays induced no clastogenic effects in the bone marrow cells of Wistar rats (Pugliesi et al, 2007). A chloroform fraction of barkwood extract induces an increase (although not a statistically significant one) in the average amount of DNA damage in peripheral blood cells of Swiss mice but also showed no clastogenic effects in the bone marrow and peripheral blood cells of the rodents (Ribeiro et al, 2009).…”
Section: Resultsmentioning
confidence: 77%
“…Plant extracts do not have obvious ways of action. Ribeiro et al (2009) showed that although the chloroform fraction of A. populnea (Reiss) Lundell shows no genotoxic or clastogenic/aneugenic effects in the bone marrow cells of Wistar rats, its crude bark wood extract shows a slight but significant increase in clastogenicity in those cells. On the other hand, Nikaidou et al (2005) showed that the catechins, important constituents of green tea, are able to reduce the mutagenic potential of hydroxyl radical.…”
Section: Discussionmentioning
confidence: 99%